Dynamics of Trust, Information Quality, and Risk Perception in Online Purchasing Decisions - Astuti , Ayu Widiya; Arafah, Willy; Nur, Aji Mohammad Fadrian (Riviera Publishing, 2024)
This study aims to analyze the influence of trust, information quality and risk perception on online purchase decisions. This research is a quantitative research with a research design using exploration. The population in this study is the overall consumer of online shop services in South Jakarta. The sampling method in this study uses purposive sampling using the Roscoe (1975) approach in determining the number of samples. The data analysis method in this study uses SEM-PLS. Based on the results of the study, it was found that trust, information quality and risk perception play an important role in influencing online purchase decisions. It was also found that the perception of risk had a significant negative effect on purchase decisions.